PROTOTIPE ALAT PEMILAH SAMPAH CERDAS BERBASIS INTERNET OF THINGS - Rio Ramadhan; Nila Feby Puspitasari (PPM Sdirjianbang Akademi Militer, 2023)
Sorting waste is the process of separating the types of waste based on their categories or characteristics. The purpose of segregating waste is to facilitate waste management in a more effective and efficient manner, as well as to support better recycling or waste management activities. One of the current problems is waste contamination. When the waste that has been separated is mixed again in the process of collecting or transporting waste. This can happen if there is no clear separation between the different types of waste or if there is negligence in the waste management process. Contamination of waste reduces the effectiveness of sorting and can hinder recycling efforts. What can be done to overcome this problem is to adopt technology to support a smarter and more sustainable waste sorting process, one of which is implementing the Internet of Things (IoT) in the waste sorting process can help increase efficiency, reduce costs, and optimize waste management efficiently. Whole. This study aims to create a prototype of an Internet of Things-based Smart Waste Sorting Tool which is expected to increase efficiency in the waste sorting process. Prototyping of this tool utilizes the Arduino Nano and Wemos D1 microcontrollers as operating centers. The input to this tool is in the form of sensors to distinguish types of plastic and paper waste using ultrasonic sensors while for metal waste using inductive sensors. To send and receive notifications using the Blynk app.